40Ar-39Ar age analyses of some intruded rocks from Mt. Riiser-Larsen in the Napier Complex - Takigami, Yutaka; Ishikawa, Naoto; Funaki, Minoru (National Institute of Polar Research, 2002)
P(論文) Three ^<40>Ar-^<39>Ar geochronological studies are performed for intruded rocks from Mt Riiser-Larsen in the Napier Complex, East Antarctica All samples have excess Ar and no ^<40>Ar-^<39>Ar plateau ages are obtained from these results Considering two previous age results, however, two metamorphic events at about 700-750 Ma and 1000-1100 Ma might have been suggested departmental bulletin paper